Design of Accounting Information System Order Menu on Codajie Cafe Using Javaweb Netbeans Ide 8.1 - Elin Panca Saputra; Fitria Dara Kurnia; Jestin Anttares; Supriatiningsih Supriatiningsih; Siti Nurajizah (Institute of Computer Science (IOCS), 2021)
Codajie Cafe is a business entity that engages in culinary field. but in fact, the Cafe doesn't yet have a system that can assist in various processes in it, such as ordering process, and sales. This café report uses conventional methods in recording and storing data. This can cause problems such as human error in the ordering process. So to solve these problems, the authors create a computerized system that is design of an accounting information system for ordering menus at a conventional codajie café to make it more efficient. In the making of this web application, the author uses Javaweb Netbeans IDE 8.1 and programming languages such as PHP, HTML, javascript, css, jquery by having several facilities such as Login, menu data, Customer data, User data, sales transaction, order, and reports that can be accessed by the company owner and the cashier. By making a computerized system, the author can help the ordering process, sales to reporting on codajie Cafe, in order to achieve effective business activities and time efficiency in company activities.